2011
DOI: 10.1007/s00345-011-0666-3
|View full text |Cite
|
Sign up to set email alerts
|

Immediate renal Doppler ultrasonography findings (<24 h) and its association with graft survival

Abstract: IRDUS can be useful, besides being highly useful in the diagnosis of graft primary dysfunction in the transplanted patient also yields information that can help to predict long-term graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
0
18
1
1
Order By: Relevance
“…It can diagnose initial graft dysfunction as well as postoperative complications. 17 In addition, Doppler ultrasound can be used to measure some indices. Resistive index is one that is an indirect indicator for degree of resistance of the intrarenal vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It can diagnose initial graft dysfunction as well as postoperative complications. 17 In addition, Doppler ultrasound can be used to measure some indices. Resistive index is one that is an indirect indicator for degree of resistance of the intrarenal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it shows the "vascular compliance" of the recipient. 17 However, RI has some limitations such as wide normal range that makes its values limited. 18 Additionally, many conditions such as acute rejection, acute tubular necrosis, venous thrombosis, hydronephrosis, and pyelonephritis can result in elevation of RI immediately after renal transplant, 17,19 whereas RI changes are not specific for any of these clinical entities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 In our study, we evaluated the day-2 RI, and the end point was a sCr of more than 1.5 mg/dL. According to measuring time of RI, the study by Barba et al 28 was nearly similar to our study, but the end point of that study (graft failure) was different. They assessed the RI performed 1 day after transplantation in 343 patients and found that graft survival was significantly lower in patients with RI greater than 0.70.…”
Section: Discussionmentioning
confidence: 59%